Geometric pinning and antimixing in scaffolded lipid vesicles - Melissa Rinaldin (Nature Portfolio, 2020)
Lipid bilayers feature an intricate interplay between membrane geometry and its chemical composition but lack of a model system with simultaneous control over membrane shape and composition prevented a fundamental understanding of curvature-induced effects. Here the authors demonstrate that the local substrate geometry and global chemical composition of the bilayer determine both the spatial arrangement and the sorting of lipid domains.